An affective computing approach to physiological emotion specificity: Toward subject-independent and stimulus-independent classification of film-induced emotions - Kolodyazhniy, Vitaliy; Kreibig, Sylvia D.; Gross, James J.; Roth, Walton T.; Wilhelm, Frank H. (Psychophysiology, 2011)
The hypothesis of physiological emotion specificity has been tested using pattern classification analysis (PCA). To address limitations of prior research using PCA, we studied effects of feature selection (sequential forward selection, sequential backward selection), classifier type (linear and quadratic discriminant analysis, neural networks, k‐nearest neighbors method), and cross‐validation method (subject‐ and stimulus‐(in)dependence). Analyses were run on a data set of 34 participants watching two sets of three 10‐min film clips (fearful, sad, neutral) while autonomic, respiratory, and facial muscle activity were assessed. Results demonstrate that the three states can be classified with high accuracy by most classifiers, with the sparsest model having only five features, even for the most difficult task of identifying the emotion of an unknown subject in an unknown situation (77.5%). Implications for choosing PCA parameters are discussed.